Novel homozygous PANK2 mutation identified in a consanguineous Chinese pedigree with pantothenate kinase-associated neurodegeneration - Li, Yan-Fang (Biomed Rep, 2016)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare autosomal recessive neurodegenerative disorder resulting from pantothenate kinase 2 (PANK2) gene mutations. It is clinically characterized by early onset of extrapyramidal symptoms, with or without pigmentary retinopathy, optic atrophy and acanthocytosis. The specific radiographic appearance of PKAN is the eye-of-the-tiger sign. However, there are few studies regarding PKAN patients of Chinese Han ancestry. In the present study, a Chinese 20-year-old female with an 8-year history of unsteady walking and involuntary movements is described. Brain magnetic resonance imaging revealed eye-of-the-tiger sign. Following sequencing of PANK2, a novel homozygous c.863C>T (p.P288L) mutation was identified in the patient and heterozygous c.863C>T was identified in her consanguineous parents. The absence of this mutation in the 1000 Genomes database, The Exome Aggregation Consortium, and 200 controls demonstrated that this mutation was probably pathogenic for PKAN in this family. In addition, the PANK2 c.863C>T mutation was predicted to be deleterious by SIFT, disease causing by Mutation Taster and probably damaging by PolyPhen2.